Initial development of a multistage cancer model based on Syrian hamster embryo (SHE) cell transformation studies - Liao, Kai-Hsin, author; Yang, Raymond Shih-hsien, 1940-, advisor; Reardon, Kenneth F., advisor; Murphy, V. A., committee member (Colorado State University. Libraries, 1999)
To better incorporate biologic information into quantitative cancer modeling, the two-stage MVK (Moolgavkar-Venzon-Knudson) model has been modified for use with SHE cell neoplastic progression. Conceptually, five phenotypic stages are included in this model: normal cells can either become senescent or mutate into immortal cells followed by anchorage-independent growth and tumorigenic stages. Cells in each stage have distinct division, death and mutation rates, and mutation is assumed to occur during cell division. Model development and related experiments were focused on studying the abilities of lead, arsenic, chromium, and a mixture of these three metals to induce progression of SHE cells from one phenotype to the next. Cell division and death rates were assessed using flow cytometric analysis for inclusion in the model. Cell division rates were measured using bromodeoxyuridine (BrdU) incorporation with propidium iodide staining, which allows for the calculation of potential doubling time, a measure of cell cycle time that takes growth fraction, but not cell loss, into account. Potential doubling times of normal SHE cells ranged from 12 to 59 hours, depending on the degree of confluence of cell cultures. Cell death was measured by a flow cytometry method based on propidium iodide staining specifically related to membrane damage. The mean cell death rate is approximately equal to 1 % of the average value of division rates. The individual metals and their mixture did not induce immortalization or further mutations of SHE cells in our laboratory following a 2-day exposure. However, the growth of SHE cells was inhibited by 5.4 μM of arsenic, with cells becoming senescent after only 16 population doublings; whereas, normal cells and cells exposed to lower arsenic concentrations lasted for at least 30 population doublings. The model developed in our laboratory successfully predicted the growth of normal cells. The cell senescence rates under the impact of arsenic exposure were also calculated. Mechanisms responsible for induction of cellular senescence in SHE cells exposed to arsenic may be involved in the apparent inability of arsenic to induce neoplasia in experimental animals.
Department Head: V. A. Murphy.
Keywords: cancer modeling; SHE cells; Moolgavkar-Venzon-Knudson model; Syrian hamster embryo cells; biologically-based dose-response model; BBDR model; MVK model; Cancer -- Research; Cancer -- Animal models